PENGARUH BRAND TRUST, SERVICE QUALITY DAN CUSTOMER SATISFACTION PADA LOYALITAS (STUDI PADA PELANGGAN GOJEK DI KOTA DENPASAR) - Desak Putu Harum Sari; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (EMAS, 2021)
Loyalty refers more to the form of behavior of decision-making units to make continuous purchases of a selected company's product. The purpose of this study was to determine the effect of brand trust, service quality and customer satisfaction on Gojek customer loyalty in Denpasar City. The population of this study were all Gojek users in Denpasar City. The sample of this research is classified as non-probability sampling with purposive sampling. The data analysis technique used to test the deep hypothesis is multiple linear regression analysis. The results showed that brand trust has a positive and significant effect on customer loyalty Gojek in Denpasar City. Service quality has a positive and significant effect on Gojek customer loyalty in Denpasar City. Customer satisfaction has a positive and significant effect on customer loyalty at Gojek in Dempasar City. This research still has many limitations, the indicators used as descriptions of the variables under study can be added again so that the information obtained will be more detailed and varied.